Theoretical Study of the Kinetics Mechanism Underlying GaN Epitaxy Growth on 4H‐SiC Substrate - Haidong Yuan; Liwei Wang; Jiangming Guo; Ruimei Yuan; Zhenhua Lin; Jincheng Zhang; Lixin Guo; Yue Hao; Jingjing Chang (Advanced Materials Interfaces)
Abstract Although GaN has successfully epitaxy growth on 4H‐SiC substrate, its kinetics mechanism, and how to control the morphology and polarity of epitaxial GaN have not been revealed yet. Herein, by investigating the epitaxial process of GaN growth on 4H‐SiC substrate, we found that the Si‐TH and C‐MT configurations are stable for Ga‐N co‐adsorption, S nucleation and epitaxy growth. Ga‐polar GaN has been found in the Si‐TH configuration, whereas potential N‐polar GaN has been realized in Si‐TM and C‐TH configurations. Besides, the predicted novel 4|8 GaN with non‐polar has been found in the C‐MT configuration, resulting from the polarity competition of GaN nucleation. Both layered GaN and novel 4|8 GaN exhibit quantum effects here. Our work not only reveals the kinetics mechanism of GaN epitaxy growth on 4H‐SiC substrate in‐depth, but also provides a potential way to control the structure and polarity of epitaxial GaN with precise configurations in situ.